The climate crisis as a catalyst for emancipatory transformation: An examination of the possible - Sturat, S. Gunderosn, and R. Petersen, B. (International Sociology)
Extinction Rebellion, Fridays for Future, and the Sunrise Movement, have received the most attention and continue to grow. Synthesizing and integrating Erik Olin Wright$1 (Bs theories of social transformation, the authors apply Wright$1 (Bs work to analyze these movements and identify barriers and opportunities moving forward. While significant forces of social reproduction continue to shape politics and constrain climate action, unintended social consequences combined with new social movements are ripening conditions for transformation. The authors identify non-reformist reforms, a forceful form of symbiotic transformation pushed forward by social movements, as the most likely strategy to address the climate crisis and catalyze broader emancipatory transformation. While climate movements face significant opposition, they continue to grow and create a stronger trajectory for deep social change.- Reproduced s
Keywords: Capitalism, Climate change, Emancipatory social science